Case Report: Nasolabial CYST - Diprasta, Made Maylisca Theresia Mulya; Setiawathi , Ni Putu (Indonesian Health Journal, 2025)
A nasolabial cyst (NC) is a rare non-odontogenic soft tissue cyst located between the upper lip and nasal vestibule. It predominantly affects women aged 40–60 years and is more prevalent in African Americans. Though uncommon, it can cause facial asymmetry and mild to moderate nasal obstruction. Diagnosis relies on physical examination identifying a nasal base mass, supported by computed tomography (CT) and magnetic resonance imaging (MRI). In this study, a 61-year-old woman presented with one-year swelling at the right nasal base. Diagnosis was confirmed via physical exams, nasoendoscopy, and contrast-enhanced CT of the nose and paranasal sinuses. Surgical excision is the primary treatment. The sublabial approach is standard, but transnasal endoscopic marsupialization offers faster recovery and fewer complications. Selection depends on cyst size, location, and facility availability. Here, the patient underwent successful sublabial extirpation under general anesthesia. Histopathology revealed pseudostratified columnar epithelium with goblet cells, confirming the diagnosis. One-month follow-up showed complete resolution, no complications or recurrence, improved facial symmetry, and high patient satisfaction. Appropriate management enhances quality of life in cosmetic and functional domains.